La familia y su incidencia en la atención integral de los adultos mayores de la parroquia urbana del Cantón Zapotillo y la intervención del trabajador social” - Mega Briceño, Martha del Cisne (2016)
The biggest adult in their newspaper to live has changed the performance scenarios, before the work, the responsibility with their children, providing the necessary thing so that their family is developed and today clerk has become with necessity of affection, support, recreation spaces, social spaces that it allows him to have a worthy life. It is so the present titled investigation work: THE FAMILY AND THEIR INCIDENCE IN THE INTEGRAL ATTENTION OF THE biggest ADULTS DE THE URBAN PARISH OF THE CANTON ZAPOTILLO AND THE SOCIAL WORKER'S INTERVENTION, during the period May 2013-February 2014; he/she had as main objective": to Gestate an intervention project that facilitates the improvement of the quality of life of the biggest Adult" by means of the active and effective participation of the family and the specific objectives of the investigation, they allowed to Base the related categories theoretically in order to study, to elaborate a diagnosis of the biggest adult's social reality, to elaborate an intervention proposal to improve the biggest adult's integral attention.. The same ones that were completed during the trial of investigation. Among the main discoveries obtained in the field investigation they allowed to determine that the biggest adults require of the implementation of structured social spaces where people of their same age converge, and they can share, to be related, to enjoy appropriate moments for their age; contributing with their knowledge, experience, vivencias to build their appropriate space, and that to say of the biggest adults they are stimuli that it allows them to recover their self-esteem provided emotional stability, increasing their physical and mental health for the implementation of the change of routines in the daily life. For another side, one can viabilizar the list of the family of the biggest adults that in first instance in some cases completes with the one of providing certain necessary inputs for the survival, in others of the cases it facilitates the care for limited times; being determined that the social list is limited by the multiple acquired responsibilities with its family. This way, same in the investigation the families zapotillences share the idea that structuring the social spaces for the biggest adults so that they improve their quality of life; and they have the bias to channel a series of administrations that they can contribute to the construction of social spaces, so that their relatives share their potentials and cumulative experiences with their equals. Concerning the methodology, the investigation was developed based on the Methodology of the leaning Scientific method of its method assistants: analytic method - synthetic, inductive method - deductive, descriptive method, historical method, statistical method for the interpretation and analysis of the results, which are shown in squares and representative charts, and this way to emit the summations, to propose and to make the respective recommendations. Likewise you uses technique as the observation, direct dialogues, the use of tools like the field newspaper, interviews and other, they were good for the obtaining of the proposed objectives. It is in and of itself that that you outlines an intervention proposal with the purpose of improving the quality of the biggest adult's life and for ende their lifestyle